An α7 nAChR approach for the baseline-dependent modulation of deviance detection in schizophrenia: A pilot study assessing the combined effect of CDP-choline and galantamine. (April 2023) - Choueiry, Joëlle; Blais, Crystal M.; Shah, Dhrasti; Smith, Dylan; Fisher, Derek; Labelle, Alain; Knott, Verner
Background: Cognitive operations including pre-attentive sensory processing are markedly impaired in patients with schizophrenia (SCZ) but evidence significant interindividual heterogeneity, which moderates treatment response with nicotinic acetylcholine receptor (nAChR) agonists. Previous studies in healthy volunteers have shown baseline-dependency effects of the α7 nAChR agonist cytidine 5′-diphosphocholine (CDP-choline) administered alone and in combination with a nicotinic allosteric modulator (galantamine) on auditory deviance detection measured with the mismatch negativity (MMN) event-related potential (ERP). Aim: The objective of this pilot study was to assess the acute effect of this combined α7 nAChR-targeted treatment (CDP-choline/galantamine) on speech MMN in patients with SCZ ( N  = 24) stratified by baseline MMN responses into low, medium, and high baseline auditory deviance detection subgroups. Methods: Patients with a stable diagnosis of SCZ attended two randomized, double-blind, placebo-controlled and counter-balanced testing sessions where they received a placebo or a CDP-choline (500 mg) and galantamine (16 mg) treatment. MMN ERPs were recorded during the presentation of a fast multi-feature speech MMN paradigm including five speech deviants. Clinical measures were acquired before and after treatment administration. Results: While no main treatment effect was observed, CDP-choline/galantamine significantly increased MMN amplitudes to frequency, duration, and vowel speech deviants in low group individuals. Individuals with higher positive and negative symptom scale negative, general, and total scores expressed the greatest MMN amplitude improvement following CDP-choline/galantamine. Conclusions: These baseline-dependent nicotinic effects on early auditory information processing warrant different dosage and repeated administration assessments in patients with low baseline deviance detection levels.